Therapeutic and Systemic Adverse Events of Immune Checkpoint Inhibitors Targeting the PD-1/PD-L1 axis for Clinical Management of NSCLC. (4th October 2021) - Chen, Jing; Alduais, Yaser; Chen, Baoan
Non-small-cell lung cancer takes up the majority of lung carcinoma-caused deaths. It is reported that targeting PD-1/PD-L1, a well-known immune evasion checkpoint, can eradicate tumor. Checkpoint inhibitors, such as monoclonal antibodies, are actively employed in cancer treatment. Thus, this review aimed to assess the therapeutic and toxic effects of PD-1/PD-L1 inhibitors in treatment of NSCLC. So far, 6 monoclonal antibodies blocking PD-1/PD-L1 interaction are identified and used in clinical trials and randomized controlled trials for NSCLC therapy. These antibody-based therapies for NSCLC were collected by using search engine PubMed, and articles about the assessment of adverse events were collected by using Google search. Route of administration and dosage are critical parameters for efficient immunotherapy. Although antibodies can improve overall survival and are expected to be target-specific, they can cause systemic adverse effects in the host. Targeting certain biomarkers can limit the toxicity of adverse effects of the antibody-mediated therapy. Clinical experts with knowledge of adverse effects (AEs) of checkpoint inhibitors can help manage and reduce mortalities associated with antibody-based therapy of NSCLC.